Measuring the price responsiveness of gasoline demand - Richard Blundell; Joel L. Horowitz; Matthias Parey (Centre for Microdata Methods and Practice (cemmap), 2009)
This paper develops a new method for estimating the demand function for gasoline and the deadweight loss due to an increase in the gasoline tax. The method is also applicable to other goods. The method uses shape restrictions derived from economic theory to improve the precision of a nonparametric estimate of the demand function. Using data from the U.S. National Household Travel Survey, we show that the restrictions are consistent with the data on gasoline demand and remove the anomalous behavior of a standard nonparametric estimator. Our approach provides new insights about the price responsiveness of gasoline demand and the way responses vary across the income distribution. We reject constant elasticity models and find that price responses vary non-monotonically with income. In particular, we find that low- and high-income consumers are less responsive to changes in gasoline prices than are middle-income consumers.
Keywords: D12; H31; C14; 330; Benzin; Nachfrage; Preiselastizität; Einkommensverteilung; Nichtparametrisches Verfahren; Schätzung; USA